Banking on knowledge : the genesis of the Global Development Network - Stone, Diane, 1964- (Warwick studies in globalisation., 2000)
Banking on Knowledge is one of the first studies of how the World Bank is reinventing itself as the 'Knowledge Bank'. The book addresses how international organizations and governments are developing partnerships with think tanks, research institutes and other knowledge institutions in the hope of informing and improving policies for reform and development around the world. The book focuses on the recently established Global Development Network (GDN). The GDN is a new and ambitious initiative, sponsored by the World Bank, which is possibly the largest worldwide non-governmental.